2022
DOI: 10.24014/jnsi.v5i1.16949
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Effectiveness of Animated Instructional Media on Academic Performance and Retention of Genetics Concepts

Abstract: The present study was carried out to assess the effectiveness of animated instructional media on academic performance and retention of genetic concepts among senior secondary school on biology students in Sokoto State. Adopted through Quasi Experimental design involving pre-test, post-test and post-posttest on two equivalent groups as experimental and control, the population on the study was 10148 SS III Biology students. In this regard, four intact classes were chosen with sample size of 238 SSIII students. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…This finding is not in consonance with Adonu et al (2021), Gambari et al (2016), andOladimeji et al (2021) whose study revealed a significant difference in the mean retention of students exposed to flipped classroom instructional approach. It also goes contrary to Faruk et al (2022) and Mogbo et al (2021) whose study on computer animation discovered a significant difference in the retention scores of students. The reason for this discovery is due to the fact that the computer simulation and animation package used in flipped classroom situation in this study incorporated videos, texts and voice mechanisms, which, for that reason, has what it takes to arouse both auditory and visual senses of learners and, in this manner, supporting them to retain the content.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This finding is not in consonance with Adonu et al (2021), Gambari et al (2016), andOladimeji et al (2021) whose study revealed a significant difference in the mean retention of students exposed to flipped classroom instructional approach. It also goes contrary to Faruk et al (2022) and Mogbo et al (2021) whose study on computer animation discovered a significant difference in the retention scores of students. The reason for this discovery is due to the fact that the computer simulation and animation package used in flipped classroom situation in this study incorporated videos, texts and voice mechanisms, which, for that reason, has what it takes to arouse both auditory and visual senses of learners and, in this manner, supporting them to retain the content.…”
Section: Discussioncontrasting
confidence: 57%
“…In another study, Ahmed and Inti (2021) revealed a substantial difference in the achievement of students exposed to animation and lecture method. Faruk et al (2022) also found a significant difference in the achievement and retention of students exposed to animation and orthodox method of teaching. In another study, Gambari et al (2014) informed a significant difference in the mean achievement and retention of students taught using animation and geometrical model.…”
Section: Open Accessmentioning
confidence: 85%
See 1 more Smart Citation
“…All implementations and modifications made are to put high considerations over the learners' abilities, needs and preferences. Faruk, Aliyu, and Hassan (2022) in their research also emphasize on "varied forms of teaching method with innovations in teaching and learning" to improve learners' learning performance. These elements are important to consider even at the initial stage of the teaching and learning preparation in order to ensure successful learning.…”
Section: Background Of Studymentioning
confidence: 99%